The Effect of Product Excellence, Satisfaction and Marketing Communication of Tabanas Products on Customer Loyalty Saving at PT. Bank Mestika Dharma Tbk, Kcp Tomang Elok Medan - Hendra Jonathan Sibarani; Bill Maximillian; Hendrik (Institute of Computer Science (IOCS), 2021)
PT. Bank Mestika Dharma, Tbk Kcp Tomang Elok Medan hopes to retain customers in the long term, even if possible forever. The purpose of this study was to examine and analyze the effect of product excellence, satisfaction and marketing communication of tabanas on customer loyalty at PT. Bank Mestika Dharma Tbk, Kcp Tomang Elok Medan. Quantitative research approach. The types of data used in this study are primary and secondary data. The population was 69 Tabanas customers who were used as a sample of 69 respondents in this study and 30 people were tested for validity and reliability. The model is with multiple linear regression. The result is product excellence, satisfaction and marketing communication of tabanas products have an effect on customer loyalty to save at PT. Bank Mestika Dharma Tbk, Kcp Tomang Elok Medan.